Analisis dan Perancangan Sistem Informasi Pendaftaran Magang Berbasis Web di Sektor Pemerintahan Menggunakan Metode RAD - Evy Nurmiati; Balqis Aulia Rahma; Musthafa Kamil (Bulletin of Computer Science Research, 2025)
Internships are a practical learning experience for students in government agencies and other sectors. However, the administrative process often faces challenges, particularly in terms of efficiency and order. This research was conducted in a government agency, focusing on the design of a web-based internship registration information system. The problem encountered was that the internship administration process still required many manual steps, potentially causing verification delays and suboptimal information delivery. To address these issues, this study employed the Rapid Application Development (RAD) method, with the main stages being requirements planning, design, implementation, and system testing. Data were collected through literature studies, observations, and system requirements analysis using the SWOT and PIECES approaches. The objective of the research was to design a prototype system capable of supporting an integrated internship registration process, from participant registration and application submission, document verification, to application status notification. The results showed that the designed system was able to improve administrative efficiency, accelerate communication between related parties, and provide transparency to interns in monitoring application status. With this system, it is hoped that agencies can reduce administrative problems and provide more effective and structured internship services.